An Examination of the Influence of Smoking Behavior on Individual Job Performance - (:unkn) unknown (Taylor and Francis Ltd., 2017)
The purpose of this paper is to investigate the relationship between smoking behavior and individual job performance at work. The hypotheses were generated upon the rationale of the study, and an empirical research was conducted. The survey was conducted on employees working in various sectors and organizations in Istanbul, Turkey. The interpretation of the statistical data revealed that there is a significant, negative and a weak relationship between smoking behavior and job performance. According to the findings of the regression analyses, there are significant and negative influences on job performance in three dimensions of smoking behaviors apart from the dimensions of smoking related injuries and occupational accidents. As a result, the total smoking behavior domain with four dimensions influenced job performance significantly and negatively. With this study’s evidences, organizations are encouraged to take precautions and actions to decrease smoking in workplaces and in individual lives, in order to achieve better individual and organizational results of well-being. © 2017 Kamla Raj.
Keywords: Behavior; Employee Health; Performance; Tobacco Use; Workplace Health